Validation D’un Questionnaire De Satisfaction Évaluant La Qualité Des Services Dans Les Hôpitaux De La Région Du Grand Casablanca - Raji, Imane; Mohssine, Naima; Chaouch, Abdelaziz (European Scientific Journal, ESJ, 2016)
The patient satisfaction measurement provides a new perspective for analyzing the performance of health services. Surveys of "satisfaction" are a source of valuable data on outcomes and care processes to enable decision makers to improve the quality of service and better meet the expectations of patients. It is essential to have appropriate collection tools that meet the requirements and methodological rigor. There are very few valid tools for measuring the perception of patients with respect to the quality of care that integrate the specificities of the Moroccan hospital setting. We considered the reliability and degree of validity of a questionnaire used to measure perceptions vis-à-vis the quality of service patients in the Moroccan context using the Cronbach alpha coefficient correlation analysis inter items. The questionnaire showed good internal consistency of four dimensions: Cronbach Alpha> 0.7, indicating good reliability and correlation <0,6 marks independence between the dimensions or construct validity. The survey also has a good acceptability. Scores calculated dimensions can be used as an indicator in a dashboard of hospital performance ,but the adoption of an iterative development process and validation is recommended.